Airports classification and priority of their reconstruction - Marintseva, K. V. (Science and Transport Progress, 2014)
Purpose. It is important for Ukraine to have a network of airports, which would promote the current and long-term implementation of air transportation needs of the population and the economics. This study aims to establish criteria of airports classification to determine their role in the development of the air transport system of Ukraine. Methodology. The methods of statistical analysis were used for the processing of data according to categories of airport productivity and geographic information system for data visualization. Findings. It is established that the existing division of Ukrainian airports into international and domestic, as well as into coordinated and non-coordinated ones is not relevant for determining the role of airport in the development of air transport system of the country and accordingly for the priority in financing of their modernization. The approach to the determination of airports classifications using analysis of performance categories was developed. Originality. Classification criterions of the airports in Ukraine are proposed: by type of activity and by the maintenance of scheduled route network. It is proposed to classify the airports by the type of activity to the primary commercial, commercial, cargo primary commercial, cargo commercial and general aviation. According to the scheduled route network maintenane it is proposed to classify the airports as the primary, non-primary and auxiliary hubs. An example of classification by the given criteria is submitted. Practical value. The value of the obtained results is in the possibility of using the proposed classification in the task of determining the priorities for financing the country's airports. As opposed to the practice of directed funding procedure in the framework of the state program of airports development, it is proposed to take into account the fact that the resumption of the functioning of the airport and/or its modernization should be as a response to effective demand of consumers (in this case, airlines), which will be the guarantors of investment return.